Effectiveness of trauma-focused psychological therapies compared to usual postnatal care for treating post-traumatic stress symptoms in women following traumatic birth: a systematic review protocol. Issue 11 (24th November 2016) - Furuta, Marie; Spain, Debbie; Bick, Debra; Ng, Edmond S W; Sin, Jacqueline
Abstract : Introduction: Maternal mental health has been largely neglected in the literature. Women, however, may be vulnerable to developing post-traumatic stress symptoms or post-traumatic stress disorder (PTSD), following traumatic birth. In turn, this may affect their capacity for child rearing and ability to form a secure bond with their baby and impact on the wider family. Trauma-focused psychological therapies (TFPT) are widely regarded as effective and acceptable interventions for PTSD in general and clinical populations. Relatively little is known about the effectiveness of TFPT for women postpartum who have post-traumatic stress symptoms. Methods and analysis: We will conduct a review to assess the effectiveness of TFPT, compared with usual postpartum care, as a treatment for post-traumatic stress symptoms or PTSD for women following traumatic birth. Using a priori search criteria, we will search for randomised controlled trials (RCT) in four databases: Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE, PsycINFO and OpenGrey. We will use search terms that relate to the population, TFPT and comparators. Screening of search results and data extraction will be undertaken by two reviewers, independently. Risk of bias will be assessed in RCTs which meet the review criteria. Data will be analysed using the following methods, as appropriate: narrative synthesis; meta-analysis; subgroup analysis and meta-regression. Dissemination and ethics: As this work comprises a synthesis of existing studies, ethical approvals are not required. Results will be disseminated at conferences and in publications.